Glucose and leucine kinetics in idiopathic ketotic hypoglycaemia. Issue 6 (27th January 2006) - Bodamer, O A; Hussein, K; Morris, A A; Langhans, C-D; Rating, D; Mayatepek, E; Leonard, J V
Abstract : Aims: To investigate glucose and leucine kinetics in association with metabolic and endocrine investigations in children with ketotic hypoglycaemia (KH) in order to elucidate the underlying pathophysiology. Methods: Prospective interventional study using stable isotope tracer in nine children (mean age 4.23 years, range 0.9–9.8 years; seven males) with KH and 11 controls (mean age 4.57 years, range 0.16–12.3 years; four males). Results: Plasma insulin levels were significantly lower in KH compared to subjects in the non-KH group. Plasma ketone body levels were significantly higher in KH than in non-KH. Basal metabolic rate was significantly higher in subjects with KH (45.48±7.41 v 31.81±6.72 kcal/kg/day) but the respiratory quotients were similar in both groups (KH v non-KH, 0.84±0.05 v 0.8±0.04. Leucine oxidation rates were significantly lower in children with KH (12.25±6.25 v 31.96±8.59 μmol/kg/h). Hepatic glucose production rates were also significantly lower in KH (3.84±0.46 v 6.6±0.59 mg/kg/min). Conclusions: KH is caused by a failure to sustain hepatic glucose production rather than by increased glucose oxidation rates. Energy demand is significantly increased, whereas leucine oxidation is reduced.